THE PLACE AND ROLE OF THE SOUTH-WEST OLTENIA DEVELOPMENT REGION WITHIN THE NATIONAL CEREAL PRODUCTION (2017-2023) - Radu Lucian PÂNZARU; Dragoș Mihai MEDELETE (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The study focused on assessing the South-West Oltenia region's significance as a key cereal producer in Romania. Data on cultivated areas and cereal production, sourced from the National Institute of Statistics, were analyzed and interpreted for the period 2017-2023 using fixed-base and structural indices along with trend dynamics. The South-West Oltenia region encompasses a total area of 2,921,169 hectares (ranked 7th nationally, accounting for 12.25% of the total), with an agricultural area of 1,796,634 hectares (7th nationally, 12.28%) and an arable area of 1,251,902 hectares (4th nationally, 13.32%).The region has convenient agro-productive conditions for practicing cereal crops, given the climatic factors and some soils found in the region (sandy soils, from the Danube meadow and from the left bank of the Jiu River, for rye cultivation).The region cultivated cereal crops on 5,294,357 hectares (averaging 15.14% of the national total) and produced a total of 24,956,413.71 tons (14.74% of the national output). The average yield per hectare was 4,588 kg (97.33% of the national average). Thus, the South-West Oltenia Region is a significant player in the national cereal market, but there is a need to enhance current performance levels to fully capitalize on the region's potential.